The role of shear strain on texture and microstructural gradients in low carbon steel processed by Surface Mechanical Attrition Treatment. (November 2015) - Moering, Jordan; Ma, Xiaolong; Chen, Guizhen; Miao, Pifeng; Li, Guozhong; Qian, Gang; Mathaudhu, Suveen; Zhu, Yuntian
Graphical abstract: Abstract: In this study, the shear strain at various depths of a low carbon steel processed by Surface Mechanical Attrition Treatment (SMAT) was measured using deformed carbide bands as internal strain markers. The shear strain gradient is found to strongly correlate with the gradients of texture, microstructure and hardness. The microhardness increases approximately linearly with shear strain, but deviates at the top surface. In the top surface, the average ferrite grain size is reduced to 60 nm with a strong {1 1 0}//SMAT surface texture.